Application of sorghum aqueous extract for the elaboration of edible coating for minimally processed ora-pro-nóbis leaves (Research, Society and Development, 2021)
Ora-pro-nóbis is an unconventional vegetable that contains high protein levels, being little explored in Brazil. Edible coatings can be applied to foods to prolong their shelf life or adding some nutrient. This study evaluated the effect of an edible coating application on minimally processed ora-pro-nóbis leaves, through microbiological, physical chemical, bioactive compounds and antioxidant activity analysis, examining its safety, stability and checking the product for a possible functional characteristic. None of the samples showed significant difference on the edible coating’s interaction with the refrigerated storage time (8 days, 7 °C). The samples were safe for consumption throughout all the evaluated time (absence of Salmonella sp., < 3 MPN/g of Coliforms at 45 °C and maximum 2,4 CFU/g of Total Yeasts and Mold). The general mean results throughout the whole refrigerated storage time evaluated for each variable were: pH = 4.62; TA = 0.82 g of citric acid/ 100 g of sample; instrumental color: L = 42.78; a* = -13.95; b* = 21.53; moisture = 87.08%; mass loss = 5.30%; carotenoids = 913.27 µg of carotenoids/g of dried sample; phenolic compounds =11.44 mg GAE/100 g of dried sample and antioxidant activity = 359.65 µmol TE/g dry basis sample.  It was concluded that the determined protocol was efficient on the minimal processing of ora-pro-nóbis. It was possible to develop an edible coating added of sorghum aqueous extract and this did not alter significantly the product’s shelf life, but there were expressive gains of phenolic compounds.